Assessing The Reliability of Radioimmunoassay for The Quantification of Testosterone, Progesterone, Luteinizing and Follicle Stimulating Hormones - Ahmed, Kazi Reazuddin; Das, Sudipto; Khan, Jinia Afrin; Sultana, Jerin; Nusrat, Mariom; Tabassum, Ilteza; Rashid, Moontaha Binte; Haque, Md Rezwan Ul; Jabin, Zeenat (Bangladesh Journal of Nuclear Medicine, 2025)
It is a standard approach to evaluate analytical processes in a laboratory routinely. Especially if it involves the study of key hormones like testosterone, progesterone, follicle stimulating hormone (FSH), and luteinizing hormone (LH), which are required for the diagnosis of various health conditions. The aim of this study was to evaluate the sensitivity, cross-reactivity, precision, parallelism, and recovery of radioimmunoassay (RIA) of these hormone parameters to establish their reliability and suitability for clinical applications. The performance parameters were evaluated by using RIA to assay several control and clinical samples as well as their dilutions and multiple combinations of mixtures. The assays showed high precision, sensitivity, selectivity, and accuracy. The result reaffirms the reliability and robustness of RIA as an analytical tool for quantification of FSH, LH, testosterone, and progesterone. Future studies on other hormone RIAs and across other laboratories are required to further validate the result. Bangladesh J. Nuclear Med. 27(2): 229-233, 2024